Freiheit und Autonomie - Christoph Engel (Max Planck Institute for Research on Collective Goods, 2003)
– Unlike its US counterpart, the German Constitution offers all-encompassing protection; in American jargon German law thus is in the Lochner era. But this generosity only applies to individual freedom, not to private governance. There are select guarantees of governance too, as for the churches and the universities. But according to general wisdom, these guarantees are enumerative. This paper challenges the general wisdom. It claims two things: there is a general protection of private governance, enshrined in article 9 Basic Law. And a constitutional guarantee of governance is fundamentally different from the guarantees of freedom. Both classes of guarantees have in common that they protect against governmental intervention. Consequently, they also share the basic doctrinal properties. A governmental act must intervene into in an activity coming under the heading of the constitutional provision. And it must fall foul of the test of proportionality. But governance is protected as an activity. Government intervenes if private governance is prevented or impeded. Such intervention can be indirect, and therefore encompass internal organisation of the private governance body, or its access to resources. Yet neither the body's property nor its potential for making money are protected directly by the pertinent constitutional freedoms. Moreover, the proportionality principle has to be applied in a way that pays due respect to the fact that private governance by definition encroaches upon the individual freedom of its addressees.
Keywords: 330